1993
DOI: 10.1144/gsl.sp.1993.071.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Tectonics and seismic sequence stratigraphy: an introduction

Abstract: The application of sequence stratigraphic models to seismic data is restricted by the vertical and spatial resolution of the data. The fundamental stratigraphic unit of the sequence stratigraphic technique is the seismically distinguished ‘sequence’ although the concept of tectonically related ‘megasequences’ is useful. Basin stratigraphy is controlled to varying degrees by eustatic sea-level change (or base level in lakes), subsidence/uplift (tectonics) and sediment supply. Three main basin types, rift-, wren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…tightness of folding) systematically moving away from the lower interface of the sandstone bed. This is the classic form of growth strata (Williams 1993); indeed, the form of laminations on this fine bed-scale mimics that imaged at scales 5-6 orders larger on seismic data (e.g. Brun & Fort 2004).…”
Section: Assessing Syndepositional Deformationmentioning
confidence: 58%
See 1 more Smart Citation
“…tightness of folding) systematically moving away from the lower interface of the sandstone bed. This is the classic form of growth strata (Williams 1993); indeed, the form of laminations on this fine bed-scale mimics that imaged at scales 5-6 orders larger on seismic data (e.g. Brun & Fort 2004).…”
Section: Assessing Syndepositional Deformationmentioning
confidence: 58%
“…The key for seismic interpretation is to identify 'growth strata' (sometimes described as 'progressive unconformities', e.g. Williams 1993). Here we use the same criteria as for seismic data but, by scaling them down from kilometres to centimetres, apply them to outcrop and well-core.…”
Section: Assessing Syndepositional Deformationmentioning
confidence: 99%
“…The stratigraphic architecture of a succession accumulated in a rifted lacustrine basin is controlled by the basin's episodic structural activities (Hubbard, 1988;Williams, 1993;Carroll and Bohacs, 1999;Feng et al, 2000). Hubbard (1988) and Williams (1993) classified synrift and post-rift strata as two kinds of first-order sequences through their studies of rifted basins on continental margins; the succession accumulated in a synrift lacustrine basin is evidently unlike that of a post-rift lacustrine basin, and they should therefore be regarded as different highorder sequences.…”
Section: Sequence Classificationmentioning
confidence: 99%
“…Hubbard (1988) and Williams (1993) proposed two classes of FS, synrift and post-rift: because the succession accumulated in a synrift lacustrine basin is clearly unlike a post-rift succession, it was suggested that they should be regarded as different high-order sequences. By this definition, a stratigraphic succession deposited during the developmental stage of a basin is regarded as an FS.…”
Section: Sequence Classificationmentioning
confidence: 99%